Effect of GFRP and CFPR Hybrid Confinement on the Compressive Performance of Concrete - Marina L. Moretti (Fibers)
Application of hybrid jackets consisting of comparatively stiff FRP materials for the seismic retrofit of substandard RC columns, aiming at reducing the risk of buckling and of brittle failure, which are typical to older columns, is a promising challenge. Given the sparsity of similar experimental data, the objective of this paper is to study the hybrid effect in concrete confined with conventional carbon- and glass- reinforced polymer fabrics (CFRP and GFRP, respectively). Twenty-six concrete cylinders, wrapped by one to three layers of CFRP and GFRP with different fiber configurations, were tested in compression. A clear hybrid effect was observed, consisting of a less brittle failure and an improved confinement as compared to the behavior of simple jackets. Furthermore, hybrid specimens, in which a CFRP layer is substituted by a GFRP layer, appear to display similar efficiency in confinement compared to specimens with a stiffer jacket consisting of more CFRP sheets, which are expected to experience 30 to 40% higher lateral pressure owing to the stiffer jacket. A design model to estimate peak concrete compressive strength and axial strain is proposed. The results are promising towards the potential application of similar hybrid jackets for the seismic rehabilitation of older RC columns.